No need for more time: Intertemporal allocation decisions under time pressure - Florian Lindner; Julia Rose (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2016)
Time preferences drive decisions in many economic situations, such as investment contexts or salary negotiations. These situations are characterized by a very short time frame for decision making. Preferences are potentially susceptible to the confounding effects of time pressure, as proposed by dual-systems theory (Evans, 2006; Kahneman and Frederick, 2002). Results of standard methods of time preference elicitation can therefore not be directly mapped to environments characterized by severe time pressure since the underlying assumption of these models is that preferences are stable. To address the stability of time preferences under time pressure, we conduct a laboratory study with 144 subjects using convex time budgets (Andreoni and Sprenger, 2012) in order to elicit time preferences with and without time pressure in a within-subject design. We find lower present-bias under time pressure compared to the condition without time pressure on the aggregate, whereas utility function curvature and long-run discounting are stable across conditions. The findings are confirmed on the individual level. Embedding our results in dual-systems theory, how information is presented can serve as a potential means to exogenously decrease present-bias under time pressure.
Keywords: C91; D12; D81; D91; 330; time preferences; time pressure; decision making; allocation decision; budget; experiment